2019
DOI: 10.1002/jcla.23088
|View full text |Cite|
|
Sign up to set email alerts
|

Pre‐miR‐27a rs895819 polymorphism and risk of diffuse large B‐cell lymphoma

Abstract: Background Recently, several studies have investigated the relationship between Pre‐miR‐27a rs895819 polymorphism and risk of various cancers. However, the relationship between rs895819 and diffuse large B‐cell lymphoma (DLBCL) has not been well known. Methods In this study, we conducted a case‐control study to explore the role of Pre‐miR‐27a rs895819 in risk of DLBCL. The PCR‐TaqMan and luciferase assays and in vitro experiments were used to evaluate polymorphism function. Results As a result, we found subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…However, the mechanism of the rs895819 SNV and its effect on its expression is unknown. Previous studies suggested that the rs895819 SNV alters the stability and/or processing of miR-27a; however, these results are conflicting, with some studies showing increased miR-27a expression [13,34], others showing decreased miR-27a expression [27,35,36], and one showing no effect of the rs895819 SNV on miR-27a expression [37]. Similarly, conflicting studies have shown a decrease, an increase, and no association between carriers of the rs895819 SNV and the risk of various cancers [16][17][18]25,38].…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism of the rs895819 SNV and its effect on its expression is unknown. Previous studies suggested that the rs895819 SNV alters the stability and/or processing of miR-27a; however, these results are conflicting, with some studies showing increased miR-27a expression [13,34], others showing decreased miR-27a expression [27,35,36], and one showing no effect of the rs895819 SNV on miR-27a expression [37]. Similarly, conflicting studies have shown a decrease, an increase, and no association between carriers of the rs895819 SNV and the risk of various cancers [16][17][18]25,38].…”
Section: Discussionmentioning
confidence: 99%
“…Besides environment and living habits, such as a sedentary lifestyle, smoking, and drinking, genetic variation also plays an important role in the development of CRC 6,7 . Rs895819 polymorphism is a single nucleotide polymorphism (SNP) located in the terminal loop of pre‐miR‐27a and has been reported to be associated with the risk of cancer, such as non‐small cell lung cancer, cervical cancer, diffuse large B‐cell lymphoma, and CRC 8‐11 . Although several studies have suggested that the rs895819 polymorphism was associated with CRC risk in Chinese population, these results need to be further confirmed 11‐13 .…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Rs895819 polymorphism is a single nucleotide polymorphism (SNP) located in the terminal loop of pre-miR-27a and has been reported to be associated with the risk of cancer, such as non-small cell lung cancer, cervical cancer, diffuse large B-cell lymphoma, and CRC. [8][9][10][11] Although several studies have suggested that the rs895819 polymorphism was associated with CRC risk in Chinese population, these results need to be further confirmed. [11][12][13] Hence, we conducted a case-control study and pooled analysis to investigate the effect of the rs895819 polymorphism on CRC risk in Chinese population.…”
mentioning
confidence: 99%
“…However, the exact pathogenesis of NHL is still not fully understood but many risk factors reported that are involved in lymphoma development. Environments as well as genetic factors are two major risk factors for lymphoma (Zhong et al, 2019;Tang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%